2019
DOI: 10.3960/jslrt.19007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management for other iatrogenic immunodeficiency-associated lymphoproliferative disorders

Abstract: Other iatrogenic immunodeficiency-associated lymphoproliferative disorders (OIIA-LPD), a category of immunodeficiency-associated LPD according to the World Health Organization classification, is associated with immunosuppressive drugs (ISDs). Several factors, including autoimmune disease (AID) activity, Epstein-Barr virus (EBV) infection, ISD usage, and aging, influence the development of OIIA-LPD, resulting in complicated clinical courses and outcomes. Most OIIA-LPD develops in patients with rheumatoid arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 172 publications
0
84
0
Order By: Relevance
“…8 Histopathology and immunophenotype, genetics and clinical characteristics, clinicopathological features, and clinical management of MTX-LPD are well summarized in other reviews. 68,69 The proportion of DLBCL in RA-LPD was approximately 60%, being higher than that in the general population (30-40%). 67,70 Another study found that DLBCL was predominant in RA-LPD before the widespread use of MTX, including in untreated RA patients.…”
Section: Ebv-positive and -Negative Mtx-lpd In Ramentioning
confidence: 99%
“…8 Histopathology and immunophenotype, genetics and clinical characteristics, clinicopathological features, and clinical management of MTX-LPD are well summarized in other reviews. 68,69 The proportion of DLBCL in RA-LPD was approximately 60%, being higher than that in the general population (30-40%). 67,70 Another study found that DLBCL was predominant in RA-LPD before the widespread use of MTX, including in untreated RA patients.…”
Section: Ebv-positive and -Negative Mtx-lpd In Ramentioning
confidence: 99%
“…The first point is the importance of multiple biopsy for MTX-LPD. MTX-LPD are mainly DLBCL and CHL, but rarely FL, 9 peripheral T-cell lymphoma, 8 etc. The pathological features are different, but all cases have the potential for tumor regression by MTX withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…8 On the other hand, clinical features of DLBCL vary, and EBV-negative cases more often require immunochemotherapy. 9 There are many predictive factors for tumor regression other than pathological features and EBV positivity such as T cell subset in peripheral blood, 11 absolute lymphocyte count after MTX withdrawal, 12 and serum lactate dehydrogenase, C-reactive protein, and soluble interleukin-2 receptor levels. 13 This case followed a different pattern of tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic stress or injury including biopsy is considered to be a trigger for SR, and occasionally, administration of corticosteroids, anti-lymphoma drugs, or infection may cause the initiation of SR. [1][2][3] We propose a possibility that, after Fig. 2.…”
Section: To the Editormentioning
confidence: 91%
“…1 SR is currently of interest for many clinicians because of an increased number of methotrexate-related lymphoproliferative disorders, and because SR is observed in many patients after withdrawal of methotrexate. 2 In terms of a mechanism, anti-tumor immune responses by host T lymphocytes reacting against tumor cells are believed to be involved in SR, 3 and several cases have recently been reported. In a recent issue of journal of clinical and experimental hematopathology (JCEH), Tanaka et al described a case of diffuse large B-cell lymphoma (DLBCL) with SR. 4 A 35-year-old man had multiple mesenteric lymphadenopathy and a thickened small intestine wall, and was diagnosed with DLBCL (germinal center origin) without infection with Epstein-Barr virus (EBV) following laparoscopic lymph node biopsy.…”
Section: To the Editormentioning
confidence: 99%